Acoustic modeling of perforated concrete using the dual porosity theory. (1st January 2017) - Carbajo, J.; Esquerdo-Lloret, T.V.; Ramis, J.; Nadal-Gisbert, A.V.; Denia, F.D.
Abstract: Perforated concrete shows nowadays a high potential for many construction and building engineering applications. This work is devoted to the analysis of the acoustic properties of perforated concrete made from arlite lightweight aggregates. Concrete produced from these materials is an environmentally friendly alternative to traditional materials and offers a higher durability, excellent strength-to-weight ratio and low cost. In particular, it is shown that the acoustic behavior of perforated concrete can be modeled using a dual porosity approach based on the knowledge of the non-acoustic properties of the matrix granular material and geometrical data. To this end, various non-perforated and perforated samples were prepared and characterized in an experimental test facility, their acoustic properties being determined through the transfer function impedance tube method. Experimental and estimated results related to the acoustic properties of a number of prepared specimens are presented, showing a good agreement. Results suggest that this approach is suitable for practical design of such materials as part of noise control systems.